Trophic ecology of Plagioscion magdalenae (Pisces, Sciaenidae) in a neotropical reservoir in the lower Magdalena River Basin, Colombia - R. A. Rojas-Luna; C. A. García-Alzate; M. Oliveros (Arxius de Miscel-lània Zoològica)
Ecologia tròfica de Plagioscion magdalenae (Pisces, Sciaenidae) en un embassament neotropical de la conca baixa del riu Magdalena, a Colòmbia.